506 Do South Asian Babies have more Congenital Heart Defects, does Consanguinity Influence it? findings from Born in Bradford Study. (October 2012) - Agadoorappa, P; Oddie, S; Gibbs, J; Pawson, N
Abstract : Background and Aims: Born in Bradford is a birth cohort study established in March 2007 to look at health and outcomes in a multi ethnic population in Bradford (UK). We aimed to establish whether South Asian children in the cohort had a higher prevalence of congenital cardiac anomalies compared to non South Asians, and evaluate association with consanguinity. Methods: Babies with cardiac anomalies in the cohort born between May 2007 and March 2010 identified using multiple ascertainment models. Ethnicity ascribed to cases using clinical records & inferred to cohort based on questionnaire responses. Data on consanguinity and other cofounders were obtained from database. Statistical analysis done by Chi square test and logistic regression. Results: Structural congenital cardiac defects=96 cases. Overall prevalence rate=8.8/1000 live births. Prevalence was significantly higher in South Asians compared to non South Asians for all cardiac anomalies (11/1000 vs 6.2/1000, P<0.05) & anomalies including only VSDs requiring surgery (8.7/1000 vs 4.4/1000, P<0.05) implying that the differences were unlikely due to ascertainment bias. Complex cardiac defects were more prevalent in South Asians, cyanotic defects were significantly higher in this group P=0.017. South Asian ethnicity (Odds-ratio=1.76, P=0.019) and consanguinity (Odds-ratio=2.002, P=0.003) significantly increased the risk for cardiac anomalies in univariate analysis. Multivariate analysis incorporating confounding factors attenuated their effect; however consanguinity remained a borderline significant predictor. Conclusions: We have demonstrated an apparent excess of congenital cardiac anomalies in South Asians in the Born in Bradford cohort. Consanguinity seemed to increase the risk for cardiac anomalies.